Influence of Work-Family Conflict, Stress and Family Supportive Supervisor Behaviour on Employee Creativity - Boakye, J. A. (University of Ghana, 2013)
The study involved a multivariate correlational design which investigated the influence of work-family conflict, stress and family supportive supervisor behavior on employee creativity. Data were collected from fourteen (14) branches of a public sector bank in the Accra metropolis using adapted versions of Scales for Work Family Conflict , Family Supportive Supervisor Behaviours (Hammer et al., 2009), Creativity (Zhou & George, 2001) and Stress (Cohen et al., 1983). Findings showed that work-family conflict (strain-based, time-based and behavioural-based conflicts) have negative relationship with employee creativity. However, this relationship was found to be mediated and moderated by stress and family supportive supervisor behaviours respectively. These findings are discussed in relation to previous studies within the framework of the componential theory of creativity. It is recommended that the firms should adopt family supportive management practices to enable employees cope with the stress of work-family conflict to enhance employee creativity.
Thesis (MPhil.) - University of Ghana, 2013